Deconstructing maternal sensitivity: Predictive relations to mother‐child attachment in home and laboratory settings. Issue 4 (22nd November 2016) - Bailey, Heidi N.; Bernier, Annie; Bouvette‐Turcot, Andrée‐Anne; Tarabulsy, George M.; Pederson, David R.; Becker‐Stoll, Fabienne
Abstract: Despite the well‐documented importance of parental sensitivity for child development, there is a lack of consensus regarding how best to assess it. We investigated the factor structure of maternal caregiving behavior as assessed at 12 months by the Maternal Behavior Q‐Sort (Pederson & Moran) with 274 mother‐infant dyads. Subsequently, we examined associations between these empirically‐derived dimensions and child attachment, assessed in the home and laboratory (final N  = 157). Three dimensions of maternal behavior were identified, corresponding fairly closely to Ainsworth's original scales. They were labeled Cooperation/Attunement, Positivity, and Accessibility/Availability. Only Cooperation/Attunement consistently predicted home‐based attachment at 15 months and 2 years, and at comparable strength to the overall sensitivity score, suggesting that this construct may be central to sensitivity. At 18 months, compared to their primarily secure counterparts, different types of laboratory‐assessed insecure attachment were associated with different patterns of maternal behavior. Mothers in avoidant relationships ( n  = 18) were low on Cooperation/Attunement and Accessibility/Availability, but fairly high on Positivity. Mothers of disorganized infants ( n  = 11) were Cooperative/Attuned but somewhat less Positive toward, and less Accessible/Available to, their infants. A multidimensional approach to parental behavior may facilitate the identification of parenting precursors of insecure parent‐child relationships.